A Case Study on the Use of Volumetric Video in Augmented Reality for Cultural Heritage - Smolic, Aljosa; O'Dwyer, Neill; Young, Gareth (My University, 2020)
Interest in the use of augmented reality (AR) is currently growing alongside advances in visual display and 3D reconstruction technologies. With the integration of volumetric video (VV), AR can be enhanced with representations of live-action actors. In this paper, we present an exploratory case-study of a museologically focused AR application that evaluated various parameters affecting the overall experience for visitors of the Long Room in the Old Library at Trinity College Dublin. Employing a volumetric 3D representation of Jonathan Swift, the benefits of applying VV in AR for a cultural heritage use-case scenario were explored. Moreover, we compared two AR platforms for this prototype application: a tablet and an HMD. For this purpose, we collected post-task opinions of the application and processed quantitative and qualitative data. The results highlighted differences between the two platforms and showed how the developed VV AR application was initially received by the users.
Proceedings of the 11th Nordic Conference on Human-Computer Interaction (NordiCHI '20), Association for Computing Machinery (ACM), Tallinn, Estonia, 2020, ISBN: 978-1-4503-7579-5.
PUBLISHED
10.1145/3419249.3420115
Estonia
Keywords: Volumetric video; Augmented Reality; User experience; Cultural heritage; Creative Technologies; Digital Engagement; Digital Humanities; Information technology in education; Multimedia & Creativity; Other